Effective suppression of Dengue virus using a novel group-I intron that induces apoptotic cell death upon infection through conditional expression of the Bax C-terminal domain - Carter, James R.; Keith, James H.; Fraser, Tresa S.; Dawson, James L.; Kucharski, Cheryl A.; Horne, Kate M.; Higgs, Stephen; Fraser, Malcolm J., Jr. (My University, 2014)
Introduction: Approximately 100 million confirmed infections and 20,000 deaths are caused by Dengue virus (DENV) outbreaks annually. Global warming and rapid dispersal have resulted in DENV epidemics in formally non-endemic regions. Currently no consistently effective preventive measures for DENV exist, prompting development of transgenic and paratransgenic vector control approaches. Production of transgenic mosquitoes refractory for virus infection and/or transmission is contingent upon defining antiviral genes that have low probability for allowing escape mutations, and are equally effective against multiple serotypes. Previously we demonstrated the effectiveness of an anti-viral group I intron targeting U143 of the DENV genome in mediating trans-splicing and expression of a marker gene with the capsid coding domain. In this report we examine the effectiveness of coupling expression of ΔN Bax to trans-splicing U143 intron activity as a means of suppressing DENV infection of mosquito cells. Results: Targeting the conserved DENV circularization sequence (CS) by U143 intron trans-splicing activity appends a 3’ exon RNA encoding ΔN Bax to the capsid coding region of the genomic RNA, resulting in a chimeric protein that induces premature cell death upon infection. TCID50-IFA analyses demonstrate an enhancement of DENV suppression for all DENV serotypes tested over the identical group I intron coupled with the non-apoptotic inducing firefly luciferase as the 3’ exon. These cumulative results confirm the increased effectiveness of this αDENV-U143-ΔN Bax group I intron as a sequence specific antiviral that should be useful for suppression of DENV in transgenic mosquitoes. Annexin V staining, caspase 3 assays, and DNA ladder observations confirm DCA-ΔN Bax fusion protein expression induces apoptotic cell death. Conclusion: This report confirms the relative effectiveness of an anti-DENV group I intron coupled to an apoptosis-inducing ΔN Bax 3’ exon that trans-splices conserved sequences of the 5’ CS region of all DENV serotypes and induces apoptotic cell death upon infection. Our results confirm coupling the targeted ribozyme capabilities of the group I intron with the generation of an apoptosis-inducing transcript increases the effectiveness of infection suppression, improving the prospects of this unique approach as a means of inducing transgenic refractoriness in mosquitoes for all serotypes of this important disease.
Keywords: Dengue; Trans-splicing; Group I intron; Ribozyme; Mosquito; Antiviral; Suppression